P‐1.2: Photoluminescence and Electrical Properties study of ITO‐stabilized ZnO Thin‐Film Transistors with different annealing temperatures. (28th November 2018) - Zhong, Wei; Li, Guoyuan; Deng, Sunbin; Yin, Xuemei; Lan, Linfeng; Chen, Rongsheng; Kwok, Hoi Sing
Abstract : Bottom‐gate thin‐film transistors (TFTs) with ITO‐stabilized ZnO channel layers were successfully fabricated by co‐sputtering of ZnO target and ITO target. We investigate the effects of the post‐deposition thermal annealing temperature on the defects inside of the ITO‐stabilized ZnO thin film and on the electrical performance of ITO‐stabilized ZnO TFTs. The beneficial effect of various annealing temperature appears because of a reorganization of the amorphous network with controlling the defect chemistry in the films indicated by photoluminescence analysis. ITO‐stabilized ZnO thin film with the annealing temperature of 300°C exhibited less intense defect emission peaks due to reduction in the number of vacancies and interstitials via filling the oxygen vacancies with O2, and diffusion of zinc interstitial to exact sites (VZn) of the system. Furthermore, We systematically investigated the impact of various annealing temperature on their performance characteristics. It was found that ITO‐stabilized ZnO TFT with annealing temperature of 300°C exhibited fairly high electrical characteristics, especially with a saturation field‐effect mobility of 27.4 cm 2 V −1 s −1 and the threshold voltage as low as −0.64 V. The implied correlation between the post‐deposition thermal treatment and the characteristics of a transistor was investigated and demonstrated by photoluminescence analysis.